Strategies for preventing and handling Murabahah troubled financing at BMT al-Bina Tasikmalaya - Delis Nurhasanah; Endang Ahmad Yani (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2021)
This study aims to determine the factors that cause Non Performing Financing of murabahah financing at BMT Al- Bina Tasikmalaya and the strategies used by BMT Al- Bina Tasikmalaya in preventing and handling non-performing financing. This research uses descriptive analysis with a qualitative approach using SWOT analysis. The stages use EFE and IFE, followed by a SWOT matrix, and the last is QSPM. The data collection techniques used were interviews, observation, and documentation, and questionnaires. The results of this study indicate that customer character is the biggest factor and a serious threat to BMT. Priority strategy analysis shows that the approach to customers is the biggest contribution in the strategy to prevent Non-Performing Financing of murabahah